Dinotopia : quest for the ruby sunstone [videorecording (DVD)] - Doi, Davis; Roche, Sean; Milano, Alyssa; Kennedy, Jamie, 1970-; Griffin, Kathy, 1960-; Gurney, James, 1958- (GoodTimes Entertainment, 2005)
Twelve-year-old Kex stows away in a lifeboat, hoping to see the world, but after being washed overboard he finds himself on an island where dinosaurs and humans coexist.